Lizard Island : science and scientists on Australia's Great Barrier Reef - Collard, Sneed B. (New York : F. Watts, 2000)
Describes the biologists who manage the Lizard Island Research Station and their activities studying and protecting the Great Barrier Reef.
Includes bibliographical references (p. 137-138) and index.
Books for the Teen Age (NYPL).
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Lizard Island Research Station (Qld.) -- Juvenile literature; Lizard Island Research Station (Qld.); Lizard Island Research Station (Qld.); Biologists -- Biography -- Juvenile literature; Coral reef ecology -- Research -- Australia -- Lizard Island (Qld.) -- Juvenile literature; Coral reefs and islands -- Research -- Australia -- Lizard Island (Qld.) -- Juvenile literature; Biologists; Coral reef ecology; Coral reefs and islands; Ecology; Biologists -- Biography; Coral reef ecology; Coral reefs and islands -- Australia -- Research; Ecology